Intravenous sodium valproate in status epilepticus: review and Meta-analysis. (2nd January 2021) - Liampas, Ioannis; Siokas, Vasileios; Brotis, Alexandros; Zintzaras, Elias; Stefanidis, Ioannis; Dardiotis, Efthimios
Abstract: Objective: Status epilepticus (SE) is a common neurologic emergency. The present study constitutes a meta-analysis of published randomized control trials (RCTs) evaluating the use of intravenous sodium valproate (VPA) in SE. Methods: MEDLINE and Cochrane databases were comprehensively searched, while retrieved RCTs and meta-analyses were manually screened. Prespecified outcome measures included seizure-cessation, 24 h-efficacy, constitute (liver enzyme increase, arrhythmias, bone-marrow suppression, hypotension and respiratory depression) and severe (life-threatening) adverse events (AEs). Evidence synthesis was performed when appropriate, using Random-Effects (RE) or Fixed-Effects (FE) model based on heterogeneity between trials (homogeneity assumed when PQ > 0.1 and I 2 < 50%). Outcomes were assessed using Odds-Ratios (ORs) and 95%Confidence-Intervals (95% CIs). Every available comparison was investigated in terms of efficacy and tolerability. Results: Thirteen studies were retrieved and five comparisons were available, four of which involved two or more studies. Results were compatible with no significant difference between VPA and Phenytoin both in terms of efficacy and tolerability [seizure-cessation: FE-OR = 1.99, 95% CI = (0.83–4.75), 24 h-efficacy: FE-OR = 1.32, 95% CI = (0.60–2.89), composite AEs: FE-OR = 0.45, 95% CI = (0.17–1.21)]. Phenobarbital proved more commonly associated with composite AEs than VPA [seizure-cessation: RE-OR = 0.68, 95% CI = (0.05–9.44), 24 h-efficacy: RE-OR = 0.88, 95% CI = (0.02–33.9), composite AEs: FE-OR = 0.26, 95% CI = (0.09–0.82), severe AEs: FE-OR = 0.30, 95% CI = (0.04–2.28)]. Diazepam was determined inferior to VPA concerning safety issues [seizure-termination: FE-OR = 0.77, 95% CI = (0.34–1.79), severe respiratory depression: FE-OR = 0.06, 95% CI = (0.01–0.48), severe hypotension: FE-OR = 0.09, 95% CI = (0.01–0.72)]. The combination of Lorazepam (LZP) with VPA and the combination of LZP with Levetiracetam presented no difference in efficacy [24h-efficacy: FE-OR = 0.68, 95% CI = (0.37–1.24)]. Conclusions: Although, additional high-quality RCTs are warranted, according to our results, VPA can be considered a safe and effective option in the management of SE.